APLIKASI CBT (COMPUTER BASED TEST) PENGARUHNYA TERHADAP INTEGRITAS AKADEMIK SISWA DI MADRASAH ALIYAH RMB - Mawih, Mawih (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The decline in academic integrity has become a serious concern in the implementation of online based exams at Madrasah Aliyah RMB Cibitung. To address this issue, the madrasah developed and implemented a CBT (Computer Based Test) application with a stricter monitoring system. This study aims to determine the impact of the CBT application on the academic integrity of students at the madrasah. The approach used is quantitative with a causal method to test the cause-and-effect relationship between the use of the CBT application and the level of academic integrity of students. The data collection technique was carried out through the distribution of questionnaires in the form of Google Forms to 121 respondents out of a total of 167 students. The analysis results indicate a significant impact of using the CBT application on improving students' academic integrity. The indicator of motivation to answer questions purely on their own has the greatest influence in this study (IAS) compared to the indicator of difficulty in opening a new tab or being locked because some students still bring multiple cell phones. Thus, if the Madrasah can be stricter with students suspected of carrying multiple phones, the impact of using the CBT application on the academic integrity of students at Madrasah Aliyah RMB Cibitung can increase. ABSTRAKPenurunan integritas akademik menjadi perhatian serius dalam penyelenggaraan ujian berbasis online di Madrasah Aliyah RMB Cibitung. Untuk mengatasi permasalahan tersebut, pihak madrasah mengembangkan dan menerapkan aplikasi CBT (Computer Based Test) dengan sistem pengawasan yang lebih ketat. Penelitian ini bertujuan untuk mengetahui pengaruh aplikasi CBT terhadap integritas akademik siswa di madrasah. Pendekatan yang digunakan adalah kuantitatif dengan metode kausalitas untuk menguji hubungan sebab akibat antara penggunaan aplikasi CBT dan tingkat integritas akademik siswa. Teknik pengumpulan data dilakukan melalui penyebaran kuisioner dalam bentuk Google Form kepada 121 responden dari total 167 siswa. Hasil analisis menunjukkan adanya pengaruh yang signifikan antara penggunaan aplikasi CBT terhadap peningkatan integritas akademik siswa. Indikator motivasi mengerjakan soal murni jawaban sendiri memiliki pengaruh terbesar di penelitian ini (IAS) bila dibandingkan dengan indikator sulit membuka tab baru atau terkunci, karena masih ada beberapa siswa membawa handphone ganda. Dengan demikian, jika Madrasah dapat lebih ketat terhadap siswa yang diindikasi membawa handphone ganda, maka pengaruh penggunaan aplikasi CBT terhadap integritas akademik siswa di Madrasah Aliyah RMB Cibitung dapat meningkat.